Sistem Informasi Evaluasi Kinerja Dosen Pada Aspek Pengelolaan Penelitian Dan Pengabdian Kepada Masyarakat Berbasis Website Pada Universitas Primakara - Karang, I Komang Aditya; Utami, Nengah Widya; Satwika, I Putu (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
Primakara University is one of the technopreneurship campuses in Bali, where Primakara University Campus routinely conducts Lecturer Performance Evaluation (EKID) activities at the end of each semester. The Lecturer Performance Evaluation process at Primakara University is still carried out manually because there is no information system in the data management process, especially the DRPM section which still has difficulties in managing lecturer research and service data. The purpose of this research is to help the lecturer's performance evaluation process, especially the DRPM section on research and service activities. This research discusses the development of a website-based lecturer performance evaluation system that focuses on aspects of research and PKM using the Extreme Programming (XP) method which begins from the planning, design, and coding to the testing stage. The results of this study are that lecturers can input research and service data into the system, then the Reviewer team can carry out the assessment process of the research and service of lecturers that have been submitted, while the DRPM section can approve and reject the proposed research and service and can arrange scheduling in the process of research and service activities.